2018
DOI: 10.1063/1.5000123
|View full text |Cite
|
Sign up to set email alerts
|

Gallium diffusion in zinc oxide via the paired dopant-vacancy mechanism

Abstract: Isochronal and isothermal diffusion experiments of gallium (Ga) in zinc oxide (ZnO) have been performed in the temperature range of 900-1050 C. The samples used consisted of a sputterdeposited and highly Ga-doped ZnO film at the surface of a single-crystal bulk material. We use a novel reaction diffusion (RD) approach to demonstrate that the diffusion behavior of Ga in ZnO is consistent with zinc vacancy (V Zn) mediation via the formation and dissociation of Ga Zn V Zn complexes. In the RD modeling, experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 22 publications
8
29
1
Order By: Relevance
“…Similar to that observed for Al, Ga doping has been shown to yield highly conductive ZnO samples [34][35][36]. In addition, the diffusion of Ga in ZnO has been demonstrated to exhibit characteristic boxlike depth profiles similar to those observed for Al [4,25,37], although holding a slightly higher diffusivity. Figure 4 shows the Al and Ga concentration vs depth distributions for the predoped sample (see Table I) Fig.…”
Section: B Dopant Diffusion Vs Fermi Level Positionsupporting
confidence: 60%
See 3 more Smart Citations
“…Similar to that observed for Al, Ga doping has been shown to yield highly conductive ZnO samples [34][35][36]. In addition, the diffusion of Ga in ZnO has been demonstrated to exhibit characteristic boxlike depth profiles similar to those observed for Al [4,25,37], although holding a slightly higher diffusivity. Figure 4 shows the Al and Ga concentration vs depth distributions for the predoped sample (see Table I) Fig.…”
Section: B Dopant Diffusion Vs Fermi Level Positionsupporting
confidence: 60%
“…This doubleacceptor behavior has also been indicated experimentally by comparing positron annihilation spectroscopy results with Hall effect data [10,23,24]. Furthermore, recent diffusion studies of Al [4] and Ga [25] in ZnO have demonstrated a quadratic dependence of the apparent diffusion coefficient on the concentration of Al or Ga. In Refs.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…14 Knowledge of temperature dependence of the band gap is also essential for controlling the desired electrical and optical properties through thermal processing, e.g., the point defect formation energy depends on the change in the band gap, which indirectly influences the resulting electrical properties and dopant diffusion behavior of the material. 2,[15][16][17] It is challenging to measure the optical band gap values at elevated temperatures with conventional methods, especially with emission-based techniques such as photoluminescence (PL) and cathodoluminescence (CL). [18][19][20] CL may in some cases also probe band gap variation with spatial resolution on the nanoscale; however, the non-radiative recombination of electron-hole pairs, and/or thermal quenching of radiative channels, effectively limit the emission of light, and thereby also the suitability of these techniques at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%